2007
DOI: 10.1021/om7008233
|View full text |Cite
|
Sign up to set email alerts
|

Niobium Bis-alkylidene Complexes Prepared by a Multi-Electron Redox Process

Abstract: High-valent niobium bis-alkylidene complexes have been structurally authenticated along with the first paramagnetic Nb(IV) alkylidene. The bis-alkylidene complexes presented in this work are thought to be generated via a redox process involving α-hydride elimination from a transient Nb(III) bis-alkyl complex. X-ray diffraction, DFT, and multinuclear NMR studies are consistent with these bis-alkylidenes having drastically different chemical environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…TheNb1ÀC42 bond length (2.041 )isslightly elongated in comparison to known niobium carbene complexes (Nb = CR 2 (), R: H, SiMe 3 1.8651(19), 1.999(2); [27] H1.9411(16); [28] H, Ph 2.026(4) [29] ), which is probably caused by the tension of the h 5 :h 1 ring structure.T he C41ÀC42 bond (1.516 )l ies in the expected range for C sp 2 ÀC sp 3 single bonds (1.51 ), [30] whereas the C26ÀC41 bond (1.554 )i ss lightly elongated compared to typical C sp 3 ÀC sp 3 single bonds (1.53 ). [30] Owing to the formation of the bond between C26 and C41, the former fulvene bond C21 À C26 is now aC sp 2 À C sp 3 single bond (1.534 ).…”
Section: Methodsmentioning
confidence: 83%
“…TheNb1ÀC42 bond length (2.041 )isslightly elongated in comparison to known niobium carbene complexes (Nb = CR 2 (), R: H, SiMe 3 1.8651(19), 1.999(2); [27] H1.9411(16); [28] H, Ph 2.026(4) [29] ), which is probably caused by the tension of the h 5 :h 1 ring structure.T he C41ÀC42 bond (1.516 )l ies in the expected range for C sp 2 ÀC sp 3 single bonds (1.51 ), [30] whereas the C26ÀC41 bond (1.554 )i ss lightly elongated compared to typical C sp 3 ÀC sp 3 single bonds (1.53 ). [30] Owing to the formation of the bond between C26 and C41, the former fulvene bond C21 À C26 is now aC sp 2 À C sp 3 single bond (1.534 ).…”
Section: Methodsmentioning
confidence: 83%
“…The Nb1−C42 bond length (2.041 Å) is slightly elongated in comparison to known niobium carbene complexes (Nb=CR 2 (Å), R: H, SiMe 3 1.8651(19), 1.999(2); H 1.9411(16); H, Ph 2.026(4)), which is probably caused by the tension of the η 5 :η 1 ring structure. The C41−C42 bond (1.516 Å) lies in the expected range for Csp2 −Csp3 single bonds (1.51 Å), whereas the C26−C41 bond (1.554 Å) is slightly elongated compared to typical Csp3 −Csp3 single bonds (1.53 Å) .…”
Section: Methodsmentioning
confidence: 74%
“…The gross geometry about the metal center in 4 closely resembles other Group 5 complexes that have the same ancillary ligand PNP but contain bisalkylidene moieties composed of CH 2 , [20] CHtBu, [21] and CHSiMe 3 . [21] It was independently found that complex 4 could be prepared from a one-pot reaction of [(PNP)VCl 2 ] [11] with excess Mg and excess Te powder, albeit not in analytically pure form. [12] Although complex 4 appears to be resistant to thermal decomposition, the choice of reactant can result in the clean substitution of one or two Te ligands.…”
mentioning
confidence: 70%